A process evaluation of a home garden intervention - Ritter, Thea; Mockshell, Jonathan; Garrett, James; Ogutu, Sylvester; Asante-Addo, Collins (BioMed Central, 2024)
Background: Most reviews of nutrition‑sensitive programs assess the evidence base for nutrition outcomes with‑out considering how programs were delivered. Process evaluations can fill this void by exploring how or why impacts were or were not achieved. This mid‑term process evaluation examines a home garden intervention implemented in a large‑scale, livelihoods improvement program in Odisha, India. The objectives are to understand whether the intervention was operating as planned (fidelity), investigate potential pathways to achieve greater impact, and provide insights to help design future home garden programs. Methodology: Data collection and analysis for this theory‑driven process evaluation are based on a program impact pathway that shows the flow of inputs, processes, outputs, outcomes, and impacts. Quantitative and qualitative data from focus group discussions, semi‑structured interviews, and a Process Net‑Mapping exercise with beneficiaries, frontline workers, and program management staff. Results: Despite a mismatch between the design and implementation (low fidelity), the process evaluation identified positive outputs, outcomes, and impacts on home garden production, consumption, income, health and nutritional outcomes, and women’s empowerment. Flexibility led to greater positive outcomes on nutrition, the adoption of sustainable agricultural practices and easy‑to‑understand nutrition models, and the likelihood of the intervention being sustained after the program ends. Conclusions: To help food systems in rural settings reduce food insecurity by utilizing more sustainable agricultural practices, we recommend that home garden interventions include instruction on easy‑to‑understand nutrition models and on how to make natural fertilizer. Finding local solutions like home gardens to help address critical supply issues and food insecurity is paramount.